Digital entrepreneurship strategy in the tourism business of the tourism 4.0 era - Kurniati, Poni Sukaesih; Suryanto, Suryanto (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This research analyzes digital entrepreneurship strategies by tourism industry players in Tourism 4.0. The research method used in this research is descriptive with a qualitative approach. Primary data sources come from the results of in-depth interviews with informants. In comparison, the secondary data sources are obtained from the search results of research results and statements of informants published in the media. The data that has been obtained is triangulated before being analyzed. The study results stated that digital entrepreneurship in the Indonesian tourism industry is multiplying. Several factors that support the growth of digital entrepreneurship include internet penetration, large population demographics, and digitization in the tourism industry. Digital entrepreneurship actors in the tourism industry are implementing several strategies to survive during and after the Covid-19 pandemic and entering the era of Tourism 4.0. This strategy successfully attracts tourists to continue to carry out tourism activities.